2023
DOI: 10.3934/jimo.2021233
|View full text |Cite
|
Sign up to set email alerts
|

The effect of rebate value and selling price-dependent demand for a four-level production manufacturing system

Abstract: <p style='text-indent:20px;'>Price rebate is only permitted when purchases made by the customer exceed a predefined limit and they later buy other items from the purchaser. There are various forms of rebate used by production companies. This study provides a deteriorating inventory model of four-level production rates and derives the rebate-value-based demand with the product selling price under shortages. This model gives preference to optimal replenishment time, ordering quantity, rebate value, and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Rahman et al [ 11 ] demonstrated the optimal strategy of an inventory system for perishable goods with hybrid demand that depended on the sales price and stock under a known fixed-ratio partial backlogging. Mishra et al [ 58 ] presented an inventory model for perishable products to maximize profit. The model had four Production-rate levels and demand dependent on rebate value.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rahman et al [ 11 ] demonstrated the optimal strategy of an inventory system for perishable goods with hybrid demand that depended on the sales price and stock under a known fixed-ratio partial backlogging. Mishra et al [ 58 ] presented an inventory model for perishable products to maximize profit. The model had four Production-rate levels and demand dependent on rebate value.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By incorporating time-and pricedependent demand, a two-stage storage production-inventory system was investigated by Aarya et al (2022). By taking rebate-value-based dependent demand into account, Mishra et al (2022) constructed a four-level production rate inventory model. They observed that customers are encouraged to acquire things when rebate marketing is used.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to this study, four levels of production rates are modelled under deteriorating inventory conditions, and the rebate value-based demand is derived from the product price under shortage conditions. It maximizes profit by optimizing replenishment time, ordering quantity, rebate value, and selling price [21].…”
Section: Literature Reviewmentioning
confidence: 99%